2(x - 1) - 4(x + 1) = 0

Question

Asked 1/24/2011 2:47:21 PM

Updated 6/13/2019 5:59:42 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

s

Expert answered|allybee|Points 7310|

Question

Asked 1/24/2011 2:47:21 PM

Updated 6/13/2019 5:59:42 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Rating

8

3x - 8 = 7 ;

3x = 7 + 8 ;

3x = 15 ;

x = 15/3 ;

x = 5

3x = 7 + 8 ;

3x = 15 ;

x = 15/3 ;

x = 5

Added 6/13/2019 5:59:42 AM

This answer has been confirmed as correct and helpful.

-(x-5)=2

Question

Updated 8/30/2014 3:15:07 PM

2 Answers/Comments

In the problem: -(x-5)=2

To get x, first we multiply the negative to the expression (x-5),

thus it becomes:

-x + 5 = 2

then we transpose 5 to the other side leaving x on the other side

-x = 2 - 5

-x = -3

x =3

The answer should have been x = 3

To get x, first we multiply the negative to the expression (x-5),

thus it becomes:

-x + 5 = 2

then we transpose 5 to the other side leaving x on the other side

-x = 2 - 5

-x = -3

x =3

The answer should have been x = 3

Added 1/24/2011 8:12:33 PM

-(x - 5) = 2

-x + 5 = 2;

5 - 2 = x;

x = 3

-x + 5 = 2;

5 - 2 = x;

x = 3

Added 8/30/2014 3:15:07 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/30/2014 3:18:06 PM]

38,918,501

questions answered

There are no comments.